Participatory planning and means-ends rationality: a translation problem - MacCallum, Diana (Routledge, Taylor and Francis Ltd, 2008)
One of the defining characteristics of the “communicative turn” in planning is the rejection of technocratic instrumental (means-ends) rationality as the principal source of legitimacy for planning procedures. Procedural quality is now seen as grounded equally in the tenets of participatory democracy: inclusiveness, reciprocity, good communication, empowerment, mutual learning. Such ideals have become widely accepted (even if they are not always well implemented in practice). However, this trend seems to have had little effect on the products of strategic planning processes—plans—which, in the public sector, seem mostly to present recommendations as the logical (instrumentally rational) response to conditions. This article discusses the step from “collaborative” process to “logical” product as a problem of translation, drawing on actor-network theory and social linguistics to activate this concept. The discussion is informed by two case studies from Australia. Though the translation problem was dealt with in a very different way in each case, the (perceived) need to produce a conventional plan negatively affected both processes' adherence to participatory ideals. In conclusion, the paper asks whether the conservativeness of the plan as a genre might have conservative effects on the practices of public planning agencies, and whether alternative modes and/or translation processes might be found to mitigate these effects.